2007
DOI: 10.1002/psc.853
|View full text |Cite
|
Sign up to set email alerts
|

Biological characterization and modes of action of temporins and bombinins H, multiple forms of short and mildly cationic anti‐microbial peptides from amphibian skin

Abstract: Genetically encoded cationic anti-microbial peptides (AMPs) are essential components of the ancient and non-specific innate immune system, which is the principal defence mechanism of all species of life, with the primary role to kill infectious microorganisms. Amphibian skin is one of the richest natural sources of such molecules, which are produced by holocrine-type dermal glands and released upon stimulation. This review highlights the attractive and unique structural/functional properties of temporins and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 102 publications
0
40
0
Order By: Relevance
“…Antimicrobial peptides have been isolated from skin secretions of the European species B. bombina and B. variegata and from the Asian species B. orientalis and B. maxima (reviewed in [27,28]). On the basis of structural similarity, these peptides may be divided into two families: bombinins and bombinins H (Fig.…”
Section: Bombinatoridaementioning
confidence: 99%
See 1 more Smart Citation
“…Antimicrobial peptides have been isolated from skin secretions of the European species B. bombina and B. variegata and from the Asian species B. orientalis and B. maxima (reviewed in [27,28]). On the basis of structural similarity, these peptides may be divided into two families: bombinins and bombinins H (Fig.…”
Section: Bombinatoridaementioning
confidence: 99%
“…Two shorter, less cationic bombinin H components with 17 amino acid residues were identified in B. orientalis skin secretions [35]. Bombinin H3 and H4 from B. variegata and bombinin H6 from B. orientalis are unusual in that isoforms have been found that contain D-alloisoleucine instead of the gene-encoded L-isoleucine and D-leucine instead of L-leucine at position 2 in the molecules [27,36]. The enzyme responsible for effecting this post-translational isomerization has been isolated from frog skin [37].…”
Section: Bombinatoridaementioning
confidence: 99%
“…However, overstimulation of the immune system, induced by excess LPS, may produce an overwhelming amount of cytokines that damage host tissues and organs (40 -42). Therefore, structures and interaction studies of AMPs with LPS are vital to better understand their mechanism of antibacterial activities and to facilitate the development of new antiendotoxic/antibacterial agents (43)(44)(45).…”
mentioning
confidence: 99%
“…Among such isoforms, temporins represent the largest family, with more than 50 members (31). They are among the smallest amphipathic ␣-helical AMPs found in nature to date (10 -14 amino acids) and contain only a few positively charged amino acids (net charge at a neutral pH ranging from 0 to ϩ3) (32,33).…”
mentioning
confidence: 99%